2015
DOI: 10.1016/j.jacc.2015.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Ectopy as a Predictor of Heart Failure and Death

Abstract: Background Studies of patients presenting for catheter ablation suggest that premature ventricular contractions (PVCs) are a modifiable risk factor for congestive heart failure (CHF). The relationship between PVC frequency, incident CHF, and mortality in the general population remains unknown. Objectives The goal of this study was to determine whether PVC frequency ascertained using a 24-h Holter monitor is a predictor of LVEF decline, incident CHF, and death in a population-based cohort. Methods We studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
203
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 265 publications
(224 citation statements)
references
References 28 publications
12
203
3
6
Order By: Relevance
“…Whereas this observation is consistent with previous data using Holter monitoring,5, 7 it underscores the impact that ectopy on a standard ECG might deliver. Of interest, much of the relationship between a PAC and subsequent death appeared to be mediated by incident AF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whereas this observation is consistent with previous data using Holter monitoring,5, 7 it underscores the impact that ectopy on a standard ECG might deliver. Of interest, much of the relationship between a PAC and subsequent death appeared to be mediated by incident AF.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, frequent premature ventricular contractions (PVCs) quantified by Holter studies are associated with incident HF and mortality 7, 8. Given evidence that successful ablation of PACs can eradicate AF9 and that successful ablation of frequent PVCs can normalize systolic dysfunction,10, 11 experts in the field now refer to ectopy as a cause of myopathy 12, 13, 14, 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…Although several reports have shown that findings on the routine ECG are associated with future HF events,8, 9, 10, 11, 12, 13, 14, 15, 16, 17 few have explored whether ECG predictors vary in their ability to distinguish between HFrEF and HFpEF. A recent examination from the Framingham Heart Study has shown that left ventricular hypertrophy and left bundle‐branch block are associated with HFrEF and that atrial fibrillation is associated with HFpEF 28.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the incidence of VPBs was associated with cardiovascular events and all-cause death. 26, 27 Furthermore, another study reported that these risks may be increased in patients with concurrent frequent VPBs and couplet VPBs as recorded by 48-h Holter ECG monitoring. 28 Previous studies have reported that ventricular hypertrophy is associated with the incidence of ventricular arrhythmia, especially in patients with hypertrophic cardiomyopathy, 29 arrhythmogenic RV cardiomyopathy 30 and congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%